Implementing a stabilizing intervention for traumatized refugees in temporary accommodations in South-West Germany - a randomized controlled pilot trial - Rzepka, Irja; Zehetmair, Catharina; Nagy, Ede; Friederich, Hans-Christoph; Nikendei, Christoph (Frontiers in Psychiatry, 2024)
The prevalence of trauma-related disorders, such as post-traumatic stress disorder (PTSD), as well as depressive or anxiety disorders, are significantly increased in refugees compared to the general population. This is due to the high risk of burdening and potentially traumatic experiences before, during and after their flight.have been sufficient to have a significant impact on the examined symptom burden.Small sample size and limited use of the exercises limit the reliability of the results.Trial registration number: DRKS00022862.